Tale of Three Databases: The Implication of Coverage Demonstrated for a Sample Query - Bar-Ilan, Judit (Frontiers in Research Metrics and Analytics, 2018)
Coverage is an important criterion when evaluating information systems. This exploratory study investigates this issue by submitting the same query to different databases relevant to the query topic. Data were retrieved from three databases: ACM Digital Library, Web of Science (WOS) (with the Proceedings Citation Index) and Scopus. The search phrase was “information retrieval”, publication years were between 2013 and 2016. Altogether 8,699 items were retrieved, out of which 5,306 (61%) items were retrieved by a single database only, and only 977 (11%) items were located in all three databases. The results from the three databases were analyzed and compared by number of publications and citations counts, for the whole time period and by year. Document types distribution and the h-indices of the retrieved datasets were also compared. The 977 items retrieved by all three databases were further analyzed, citations were also compared to altmetric data for these publications, collected from Mendeley.